2018
DOI: 10.1101/460576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intense and sustained pain reduces cortical responses to auditory stimuli: implications for the interpretation of Heterotopic Noxious Conditioning Stimulation in humans

Abstract: Phasic pain stimuli are inhibited when they are applied concomitantly with a conditioning tonic stimulus at another body location (Heterotopic Noxious Conditioning Stimulation, HNCS). While this effect is thought to rely on a spino-bulbospinal mechanism in animals (Diffuse Noxious Inhibitory Controls, DNIC), the underlying neurophysiology in humans may further involve other pathways. In this study, we investigated the role of supraspinal mechanisms in HNCS by presenting auditory stimuli during a conditioning… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…This finding is also in line with earlier research, wherein lower EP amplitudes were reported during a CPM paradigm [5]. At present, it is debated whether this is a biomarker of DNIC efficiency, or just habituation to the stimulus [4,17]. Evaluation of the EEG data with analyses of more statistical power such as an LMM [18] could be helpful in evaluating the influence of the individual stimulus parameters to the signal.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is also in line with earlier research, wherein lower EP amplitudes were reported during a CPM paradigm [5]. At present, it is debated whether this is a biomarker of DNIC efficiency, or just habituation to the stimulus [4,17]. Evaluation of the EEG data with analyses of more statistical power such as an LMM [18] could be helpful in evaluating the influence of the individual stimulus parameters to the signal.…”
Section: Discussionsupporting
confidence: 87%
“…This network shows activity increases upon detection of salient targets, especially when they appear in unexpected locations [48]. Of note, the most important factor in the visual network is sensing the physical metrics of the spatial layout [49], and the auditory network is primarily active when external stimuli are received [50]. In addition, the frontoparietal network can maintain control signals online in working memory from one or a small number of trials to the next, enabling it to implement task control on a faster trial-to-trial basis [51].…”
Section: E Functional Network Reliability In the Resting Statementioning
confidence: 99%
“…Specifically, activation of TRPV1‐positive fibres (mainly nociceptors), induces hypoesthesia in humans (Magerl & Treede, 2004), meaning that the stimulation of one type of afferents could influence the processing of other, heterosynaptically connected, pathways. Moreover, synaptic plasticity is not the only potential mechanism, as our protocols are likely to activate other systems, such as descending modulation, autonomous nervous system or supraspinal mechanisms (Lin et al, 2020; Torta et al, 2019).…”
Section: Discussionmentioning
confidence: 99%